Biochemistry and genetics of mannan-binding lectin (MBL). (1st August 2003) - Presanis, J.S.; Kojima, M.; Sim, R.B.
Abstract : Mannose- or mannan-binding lectin (MBL) is a member of the collectin protein family, which includes lung surfactant proteins SP-A and SP-D. Each member consists of similar or identical polypeptide chains with a region of collagen-like sequence followed by a C-type lectin domain. The polypeptides associate in threes to form a subunit containing a collagen-like helix, with three clustered lectin domains. These subunits associate into larger structures, usually with 12–18 polypeptides. The collectins bind to patterns of neutral sugars on surfaces (e.g. of micro-organisms) and mediate effector functions associated with killing/phagocytosis. MBL is the only collectin which activates complement. It resembles in quaternary structure the complement protein C1q, which recognizes targets via charge clusters. Binding of MBL to a surface activates MBL-associated serine proteases (MASPs) attached to MBL, and MASP-2 activates complement proteins C4 and C2. The MASPs are homologous to the C1q-associated proteases, C1r and C1s. MBL therefore activates complement by a mechanism very similar to C1q, and engages the opsonic activity of complement to clear micro-organisms. The serum concentration of MBL is very variable in humans. The variability is largely associated with mutations leading to amino acid substitutions in the collagen-like region which decrease MBL assembly and stability. Many studies demonstrate that MBL deficiency is associated with susceptibility to a range of infectious and inflammatory diseases.